Penggunaan Metode Demonstrasi Untuk Meningkatkan Hasil Belajar IPA Siswa Pada Materi Energi Dan Perubahannya Di Kelas V SDN 001 Kepenuhan Kabupaten Rokan Hulu - Hafyanimar Hafyanimar (STKIP Rokania Pasir Pangaraian, 2018)
In the process of education and discussion cannot be done if the process does not use the right method, because the method used is very important and can not be ignored in the learning process. Therefore the teacher must be careful in choosing the right method to deliver material to students. The essence of the method is a harmonious way and must be used by the teacher in a predetermined definition, with full responsibility, mistakes in education that will damage the educational process are free. can be done with the same method, for that the teacher must have the expertise to determine the most appropriate method for every condition and condition. One method that must be used by the teacher is the method used, a clear method can be done by the teacher and students both in individual learning and learning by the group, through this method it will be easier to observe, classify and draw conclusions from what sees it. By way of learning the teacher will easily develop the ability of students as well as make it easier for students to understand the material because they see it in person